Endometriosis and IVF treatment outcomes: unpacking the process - Edgardo Somigliana; Letizia Li Piani; Alessio Paffoni; Noemi Salmeri; Michele Orsi; Laura Benaglia; Paolo Vercellini; Paola Vigano' (BMC, 2023)
Abstract Advanced endometriosis is associated with a reduction of IVF success. Surgical damage to the ovarian reserve following the excision of endometriomas has been claimed as a critical factor in the explanation of this detrimental effect. However, it is generally inferred that other mechanisms might also hamper IVF success in affected women. They include diminished responsiveness to ovarian stimulation, altered steroidogenesis, a decline in oocyte quality, reduced fertilization and embryo development, and impaired implantation. To navigate these limitations, we scrutinized available literature for studies specifically designed to address distinct phases of the IVF process. Utmost consideration was given to intra-patient ovarian response comparisons in women with unilateral endometriomas and to studies applying a meticulous matching to control confounders. The following observations have been drawn: 1) endometriosis has a negligible impact on ovarian response. A slight reduction in stimulation response can only be observed for endometriomas larger than 4 cm. Follicular steroidogenesis is unaffected; 2) oocyte quality is not hampered. Fertilization rates are similar, and intracytoplasmic sperm injection (ICSI) is not justified. Embryonic development is uncompromised, with no increase in aneuploidy rate; 3) endometrial receptivity is either unaffected or only slightly impacted. In conclusion, our study suggests that, aside from the well-known negative effect on ovarian reserve from excisional endometrioma surgeries, endometriosis does not significantly affect IVF outcomes.